MIM, experience museum: Interview with Orieta Rojas y Milene Ramírez - Jorquera, Daniela (Base Diseño e Innovación, 2016)
The MIM—an iconic museum in the Chile of the new millennium—started operating in 2000 in the Municipality of La Granja in the Metropolitan Region of Santiago. Opening up the possibility for everyone to discover scientific knowledge, the museum became the perfect example of the way design can help deliver educational contents.